New synonyms for South American/Brazilian Pottiaceae (Bryophyta) - Da Costa, Denise Pinheiro (Phytotaxa, 2014)
During a taxonomic review of Pottiaceae in Brazil, five new synonyms were discovered for species in the genera Hyophila, Pseudosymblepharis, and Weissia.